THE INFLUENCE OF THE DRIVING SPEED OF THE TRAVELING MECHANISM OF THE COAL MINING MACHINE ON THE RANDOM LOAD OF THE ROLLER - MAO Jun; WANG Xin; CHEN HongYue; ZHANG Yu (Jixie qiangdu)
In order to study the traction speed of shearer drum load effect,the establishment of cutting part and the traction part are mutually coupled system dynamics model,and consider the cut cutting impedance is a random quantity,obey the law of normal distribution,using numerical simulation method to solve the problem and the results using statistical methods to calculate the shearer drum to force the average value and the standard difference; the results of the study show that,the drum to the mean and variance of the force with the initial traction speed of increased progressively. Finally,the accuracy of the model is verified by comparing the simulation results with the experimental measurements.